Optimization of cylindrical grinding parameter for the high product quality subject to roundness constraint - Mohd Muhyiddin, Ibrahim (2010)
In the manufacturing cylinder rod industry, final roundness of a product is very important to determine the products quality. Good roundness not only ensures good quality, but also reduces manufacturing costs. Final roundness is a important aspect of tolerance, it reduce installation time and reduce operating hours at the same time to reduce the overall cost. In this study, the main objective is to study the effect of work piece diameter, work speed and cutting depth of the roundness error in the process of cylindrical grinding by using outside cylindrical grinding machines. Roundness errors measure by using roundness measuring machine. The results of experimental analyze by using statistical methods with the help of DOE software. Based DOE method, the experiment was run by using the full factorial method and the results were analyzed using the Statistica software. The correlation for roundness error with the cutting parameters satisfies a reasonable degree of approximation. Depth of cut is the most significant parameter in affecting the roundness error workpiece. The optimal parameters are, for workpiece diameter is 18.71mm, for speed is 74.96rev/min and for depth of cut is 15.91μm.